A theoretical insight for solvent effect on myoglobin assay of W(CO)(4)L-2 type novel complexes with DFT/TDDFT - Ustun, Elvan; Demir, Serpil; Coskun, Feyzullah; Kaloglu, Murat; Sahin, Onur; Buyukgungor, Orhan; Ozdemir, Ismail (Elsevıer scıence bv, po box 211, 1000 ae amsterdam, netherlands, 2016)
Novel tetracarbonyl complexes of type W(CO)(4)L-2 (L: 4-chlorobenzylimidazoline; 4-methylbenzylimidazoline; 3,5-dimethylbenzylimidazoline; 2,4,6-trimethylbenzylimidazoline; 2,3,5,6-tetramethylbenzylimidazoline) were synthesized. Then newly synthesized novel compounds were characterized by IR, H-1 NMR, C-13 NMR and LC-MS. The characterizations of two of the complexes have also been confirmed with single crystal X-Ray diffraction and OFT optimization results of these complexes have been compared with single crystal results. We have investigated the solvent effect on the structure and metal-to-ligand charge transfer (MLCT) transitions with OFT/TDDFT calculations with ORCA package program with BP86 functional. (C) 2016 Elsevier B.V. All rights reserved.